Analysis of the Effect of Brand Image and Promotional Mix on the Purchase Decision of Oriflame Cosmetic Products in Pt. Orindo Alam Ayu Medan - Sahat Parulian Remus Silalahi; Jon Henri Purba (East Asian Journal of Multidisciplinary Research, 2022)
Purchasing decisions are decisions made by consumers to make a purchase of a product initiated by an awareness of the fulfillment of needs and desires. Many factors influence consumer purchasing decisions on company products, including brand image and marketing mix. This research is a survey research with an associative quantitative approach which aims to determine the effect of brand image and promotion mix on purchasing decisions of cosmetic products at PT. Orindo Alam Ayu (Oriflame Medan Branch). The population is all customers of PT. Orindo Alam Ayu (Oriflame Medan Branch) as many as 1247 people. Determination of the sample using the Slovin formula in order to obtain 93 research samples. The research instrument used a questionnaire and data analysis using multiple linear regression analysis. The results of the study prove that the brand image and promotion mix simultaneously have a positive and significant effect on purchasing decisions. Brand image partially has a significant influence on purchasing decisions. Promotional mix partially has a significant influence on purchasing decisions. To PT. Orindo Alam Ayu Medan is advised to further improve the promotion mix so that purchasing decisions can be maximized.